Courtney Sullivan. The Evolution of the French Courtesan Novel: From Chabrillan to Colette. London: Palgrave Macmillan Publishers, 2016. - Zoe Petropoulou (Studies in 20th & 21st Century Literature, 2018)
Review of Courtney Sullivan. The Evolution of the French Courtesan Novel: From Chabrillan to Colette. London: Palgrave Macmillan Publishers, 2016. ix +127pp.
Keywords: courtesans; French literature